Pengaruh Durasi Terhadap Retensi Audiens Dalam Motion Graphic Wajib Pajak Non Efektif - Muhammad Farhan Alkautsar; Muhammad Sukriyatma; Daffa Akmal Aminuddin; Amata Fami (Jurnal Riset Rumpun Seni, Desain dan Media, 2024)
The aim of this research is to see the effect of motion graphic duration on audience retention levels when conveying information about non-effective taxpayers and also to make recommendations for optimal duration to increase audience retention by using non-effective taxpayer motion graphics as a case study. A quantitative approach with a correlational type was used in conducting this research, as well as the use of YouTube Analytics to analyze data on audience retention levels while watching motion graphics. This research found a significant linear relationship between the duration of motion graphics and audience retention based on the motion graphics presented. A duration that exceeds three minutes can decrease audience retention.